Silver Nanofunctionalized Stent after Radiofrequency Ablation Suppresses Tissue Hyperplasia and Bacterial Growth - Yubeen Park; Dong-Sung Won; Ga-Hyun Bae; Dae Sung Ryu; Jeon Min Kang; Ji Won Kim; Song Hee Kim; Chu Hui Zeng; Wooram Park; Sang Soo Lee; Jung-Hoon Park (MDPI AG, 2022)
Intraductal radiofrequency (RF) ablation combined with placement of a self-expandable metal stent (SEMS) for malignant biliary obstruction has risks such as stent- and heat-induced biliary sludge and restenosis. Here, we investigated the efficacy of a silver nanoparticles (AgNPs)-coated SEMS to inhibit tissue hyperplasia and bacterial growth caused by RF ablation with stent placement in the rabbit bile duct. The release behavior and antibacterial effects of AgNPs-coated SEMSs were evaluated. Then, SEMSs were successfully placed in all rabbits immediately after RF ablation. Ag ions were rapidly released at the beginning and then showed a gradual release behavior. The AgNPs-coated SEMS significantly inhibited bacterial activity compared to the uncoated SEMS (p < 0.05). Cholangiography and histological examination confirmed that the level of tissue hyperplasia was significantly lower in the AgNPs group than in the control group (all p < 0.05). Immunohistochemistry analyses revealed that TUNEL-, HSP 70-, and α-SMA-positive areas were significantly lower in the AgNPs group than in the control group (all p < 0.05). Intraductal RF ablation combined with nanofunctionalized stent placement represents a promising new approach for suppressing thermal damage as well as stent-induced tissue hyperplasia and bacterial growth.